Production of low impurity aluminium rotor for motor efficiency enhancement - Savitri Payakkapol; Nattapon Chayopitak; Panya Kunsuwan; Naoto Ohtake; Sompong Srimanosaowapak (My University, 2018)
Induction motors have been widely used in various electrical applications. However, their efficiency are still limited due to losses occurring during operation, especially for smaller ratings. Higher the electrical conductivity of motor rotor by lower its impurity content is one of practical and simple way to improve motor efficiency. The aim of this work is to reduce the impurity content of aluminium rotor by addition of boron in the form of Al-5wt%B master alloy and Na 2 B 4 O 7 -NaCl-KCl flux, and then sedimention of their precipitated particles. The purer melt was then cast as rotors for single-phase induction motors. With the amount of addition of boron in aluminium melt in this work, boron in Al-5wt%B master alloy was more pronounced in removing impurities in aluminium melt than that in Na 2 B 4 O 7 . It was found that the rotors made of aluminium melt with lower impurity contents and hence higher electrical conductivity resulted in more enhancement of motor efficiency.
Keywords: Aluminum Alloys Composites Properties